Effects of creating a jejunal pouch on postoperative quality of life after total gastrectomy: A cross‐sectional study. Issue 1 (8th September 2021) - Tsuji, Toshikatsu; Isobe, Taro; Seto, Yasuyuki; Tanaka, Chie; Kojima, Kazuyuki; Motoori, Masaaki; Ikeda, Masami; Nitta, Toshikatsu; Oshio, Atsushi; Nakada, Koji
Abstract: Aim: Total gastrectomy results in the complete loss of gastric function and the development of severe postgastrectomy syndrome. During the jejunal pouch procedure following total gastrectomies, a substitute stomach is created to alleviate the effects of postgastrectomy syndrome. However, the procedure's effectiveness remains controversial. This study aimed to explore the effect of jejunal pouch creation after total gastrectomy on postoperative quality of life. Methods: A nationwide multi‐institutional cross‐sectional study, the Postgastrectomy Syndrome Assessment study NEXT, used the Postgastrectomy Syndrome Assessment Scale‐45 questionnaire to explore the optimal gastrectomy procedure for cancer located in the upper third of the stomach or around the esophagogastric junction. The questionnaire consists of 45 items consolidated into 19 main outcome measures relating to postgastrectomy symptoms, amount of food ingested, quality of ingestion, ability for working, level of satisfaction for daily life, and the physical and mental component summary of the 8‐Item Short Form Health Survey. Eligible completed questionnaires were retrieved from 1909 patients. Of these, the data were analyzed for 1020 patients who underwent total gastrectomy and 93 patients who underwent jejunal pouch creation after total gastrectomy. Results: Postoperative quality of life was compared between patients with and without pouches. The analysis revealed that patients with pouches, particularly oral pouches, experienced substantially improved postoperative quality of life than those without, even after adjusting for several clinical factors using multiple regression analyses. Conclusion: The results suggest that total gastrectomy with jejunal pouch creation, particularly oral pouches, may significantly improve postoperative quality of life. Abstract : Creating a jejunal pouch for patients undergoing total gastrectomy helps reduce postgastrectomy syndrome and improve postoperative quality of life. Oral pouches seem to be particularly successful in providing patients relief from postgastrectomy syndrom.